Rare Testicular Tumor Discovered by Assault: An Unusual Presentation of a Primary Testicular Neuroendocrine Tumor Grade 2 - Jonathan R. Epperson; Necia M. Pope; Margaret J. Abuzeid (Hindawi Limited, 2013)
Testicular neuroendocrine tumors (NET) or carcinoid tumors are rare neoplasms which represent 1% of all testicular tumors and can be divided into 3 subgroups: pure primary testicular NET, primary testicular NET associated with a teratoma, and NET metastases to the testis. We report an unusual presentation of a primary testicular neuroendocrine tumor in a 39-year-old male who presented after a physical altercation during a soccer game. Histology showed a diffuse infiltrating tumor with extensive involvement of the tunica albuginea and tunica vaginalis. Immunohistochemical expression of CD56, synaptophysin, and chromogranin A was strongly positive in the tumor cells. Foci of tumor cell necrosis and occasional mitotic figures as well as extensive lymph-vascular invasion were also identified. A review of the literature reveals differing opinions on the prognostic significance of primary tumor size, mitotic index, tumor necrosis, and nuclear atypia. In our patient, the increased mitotic rate (3-5 mitotic figures per 10 hpf and a Ki-67 index of 5%), foci of necrosis, and mild to moderate nuclear atypia warranted a diagnosis of neuroendocrine tumor grade 2, formerly atypical carcinoid. Long term surveillance in these patients is essential as metastasis occurs in up to 15% of cases. At the 6-month followup, the patient remains symptom free.